Synoptic and cloud-scale aspects related to an extreme rainfall event that occurred in April 2019 in the city of Rio de Janeiro (Brazil) - da Silva, Fabricio Polifke (2024)
The development, rate, and duration of extreme rainfall events over a region depend on the coexistence and strength of multiple atmospheric physical conditions. Then, understanding the synoptic and cloud-scale aspects is a continuous, crucial integrated task between universities and operational centers aiming for early warning and risk management. This study first evaluates the large-scale atmospheric circulation, instability behavior, and moisture parameters before and after the start of rainfall. It also investigates the dynamic triggering for an extreme rainfall event in Rio de Janeiro between April 08th and 09th, 2019. Secondly, this study intended to examine the microphysics cloud aspects using data from the Geostationary Operational Environmental Satellite (GOES-16). From monthly records and the 99th percentile of accumulated daily rainfall, it was possible to highlight the spatial rainfall dependence on seasonal and topography with higher rainfall values recorded in the south portion of the city of Rio de Janeiro. From the large-scale synoptic aspects, concomitant circulations related to upper, middle, and lower atmospheric levels creating a dynamic vertical structure favorable to convective development were verified over southeastern Brazil. The thermodynamic parameters showed different characteristics before and after rainfall started, suggesting multi-parameters' importance as so-called "instability ingredients" for evaluating the atmospheric potential for clouds and rainfall development. The velocity divergence in upper atmospheric levels was a determinant dynamic forcing for deep convection evolution. Lastly, regarding the wind circulations, northwest winds before precipitation and a change in wind direction were related to the region's frontal systems passage. The cloud microphysics aspects showed that the channel differences approach showed that monitoring top cloud glaciation, vertical development, and particle size are indicators of heavy rainfall when the cloud top offering considerable vertical growth was a helpful tool to identify regions with huge potential to develop heavy rain.